Advanced light trapping scheme in decoupled front and rear textured thin-film silicon solar cells. (1st March 2018) - Isabella, O.; Vismara, R.; Linssen, D.N.P.; Wang, K.X.; Fan, S.; Zeman, M.
Highlights: Clear assessment of merits and faults of optical performance limits and benchmarks. Thorough optimization of geometrical and material properties of modelled structure. Obtained (implied) performance exceeds theoretical predictions. Critical analysis of the modelled light trapping phenomena. Highest reported light trapping efficiency (LTE) of 1.15. Abstract: We present the study of an advanced light trapping scheme applied to thin-film silicon-based solar cells, overcoming the broadband Green absorption limit, that is the generalized case of the 4 n 2 classical absorption limit for all wavelengths. This result is achieved by the 3-dimensional optical modelling of a fully functional thin-film hydrogenated nano-crystalline silicon (nc-Si:H) solar cell endowed with decoupled front and back textures. Our results stem from rigorously characterized optical properties of state-of-the-art materials, optimized geometric nano-features on the front and rear surfaces of the solar cell, and thickness optimization of the front transparent oxide. The simulated improvements derive from a gain in light absorption, especially in the near-infrared part of the spectrum close to the band gap of nc-Si:H. In this wavelength region, the material is weakly absorbing, whereas we now find significant absorptance peaks that can only be explained by the concurrent excitation of guided resonances by front and rear textures. This insight indicates the need to modify the temporal coupled-mode theory, which fails to predict the absorption enhancement achieved in this work, extending its validity to the case of decoupled front/back texturing. Our approach results in substantially high photocurrent density (>36 mA/cm 2 ), creating a platform suitable for high efficiency single and multi-junction thin-film solar cells based either on typical silicon alloys or on the novel and promising barium (di)silicide (BaSi2 ) absorber. In the latter case, using the same advanced light trapping employed for nc-Si:H, we demonstrate a very high implied photocurrent density of 41.1 mA/cm 2, for a device endowed with 2-μm thick absorber.